Acute necrotizing otitis media in infant: a rare and challenging case - Hajare, Priti S.; Soni, Samanvaya; Patil, V. D.; Havaldar, Rajesh R.; Mudhol, Ramesh S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Acute necrotizing otitis media (ANOM) is a highly virulent middle ear infection that results in necrosis of the tympanic cavity. Here a rare case report is presented of a 4 month infant who presented with bilateral ANOM and right facial nerve palsy which was aggressively managed with debridement and intravenous antibiotics obviating the need of surgery. The child was followed up for a period of 6 months where both the ears remained disease free accompanied with hearing gain and grade of facial palsy improvement from grade V to grade II. ANOM is still a possibility in the modern era of higher antibiotics and a high index of suspicion is required. Timely and aggressive management has to be done in order to prevent the dreaded complications and sequelae like facial nerve palsy and hearing loss which are likely to be permanent.